Accessible and cost-effective deployment of environmental DNA (eDNA) samplers for sediment conducive to supporting community-based surveys - Anna H. Dema; Ellika M. Crichton; Neha Acharya-Patel; Lauren C. Bergman; Michael J. Allison; Matthew T. Bonderud; Jacob J. Imbery; Clifford L.K. Robinson; Jacqueline R. Huard; Caren C. Helbing (PLoS ONE, 2026)
The presence of at-risk, invasive, and sentinel species are measures of biodiversity, however it is often challenging to quickly gather reliable data through conventional, time-constrained surveying techniques. Environmental DNA (eDNA) detection is one method that has proven to be extremely useful for biomonitoring, particularly due to its non-invasive nature, cost efficiency, sensitivity, accuracy, and relative ease to carry out in the field. Conventional sediment sampling presents a challenge to obtain suitable representative samples and there is a need for easily accessible methods that are compatible with community-based monitoring activities and budgets. Herein, we introduce a “FloppE-Dip” method, a passive sampling approach that is compatible with larger sand sediment sample volumes up to 180 mL and utilizes easily accessible materials. We compared the FloppE-Dip method to conventional filtration through the detection of several species’ DNA from environmental samples using real-time quantitative PCR (qPCR). In a laboratory study using an American bullfrog ( Rana [Lithobates] catesbeiana ) tissue slurry, we determined optimal protocol parameters that were then applied in a field survey to identify beaches in coastal British Columbia used by the important forage fish, the Pacific sand lance ( Ammodytes personatus ). Of the 20 sampling sites, both FloppE-Dip and conventional filtration methods detected Pacific sand lance eDNA at 14 of them, albeit FloppE-Dip copies/L estimates were typically 5–10 times lower. Two sites returned no detections for both methods, and four sites returned low detections using conventional filtration methods where the FloppE-Dip method showed no detection. This discrepancy at low copy numbers may be rectified through increasing the number of samples taken per site and/or increasing the number of technical replicates. Overall, the FloppE-Dip method was more reliable than visual observation and is considerably faster and cheaper than filtration making it well-suited for general detection purposes. While other sediment types remain to be tested, the simplicity, efficiency, and use of readily available materials make FloppE-Dip a viable alternative for community-based monitoring programs, particularly given the time and budget constraints these programs often face.